Lesser relevance markers in Chinese academic spoken English corpus: a cross-disciplinary study on pragmatic features - Yu, Yang; Zeng, Gang (Frontiers in Psychology, 2023)
This study explores the usage characteristics and pragmatic functions of lesser relevance markers in academic spoken English lectures presented by Chinese scholars. A qualitative and quantitative approach is employed using the Chinese Academic Spoken English Corpus (CASEC), which encompasses disciplines in science, engineering, humanities, and social sciences. The findings reveal that Chinese scholars use lesser relevance markers less frequently compared to native English speakers. These differences in usage highlight the influence of language background, disciplinary culture, and communication conventions on the realization of informing evaluation, topic handling, and interactivity. Furthermore, within the Chinese scholars' group, humanities and social sciences scholars tend to use lesser relevance markers more frequently than science and engineering scholars. This research enhances our understanding of the multifaceted pragmatic roles of lesser relevance markers and offers insights into cross-cultural academic communication and English teaching.